Laser processing of high performance grinding wheels. (25th June 2007) - Jackson, Mark J.; Robinson, Grant M.; Chen, Xun
High performance grinding is a process that produces engineering components with a desired surface roughness. The grinding efficiency of vitrified grinding wheels deteriorates as the sharp cutting edges become blunt due to the formation of wear flats. Dressing is essentially a sharpening operation designed to generate a specific topography on the working surface of the grinding wheel. The use of high power lasers is being explored as a non-contact cleaning and dressing technique. In the present study, a high power laser was used to clean metal chips from the surface of the grinding wheel and to dress the wheel by causing phase transformations to occur on the surface of vitrified grinding wheel. Experimental results indicated that laser modified grinding wheels are comparable in performance to conventionally cleaned and dressed grinding wheels.